2006
DOI: 10.1088/0963-0252/15/2/002
|View full text |Cite
|
Sign up to set email alerts
|

On the reliability of low-pressure dc glow discharge modelling

Abstract: Modelling approaches used for the description of the cathode region of dc glow discharges are reviewed, with the focus on hybrid models which combine the fluid description of positive ions and bulk electrons with the kinetic simulation of fast electrons. The reliability of the calculated discharge characteristics is analysed by testing the different assumptions of the models and the sensitivity of the calculated characteristics on the input data. The applicability of the particle-in-cell technique (complemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 74 publications
0
76
0
Order By: Relevance
“…Recent complex numerical models [32][33][34][35][36][37][38][39], categorized as fluid, kinetic (Monte Carlo), and hybrid (combination), have shown that the modeled discharge characteristics are seriously influenced by the accuracy of the input data. Models require realistic cross sections for electron, ion, atom and photon collisions with the gas, as well as realistic probabilities for electron, ion, atom and photon interactions with electrode surfaces.…”
Section: The Role Of Ion-induced Electron Emission In Glow Dischargesmentioning
confidence: 99%
“…Recent complex numerical models [32][33][34][35][36][37][38][39], categorized as fluid, kinetic (Monte Carlo), and hybrid (combination), have shown that the modeled discharge characteristics are seriously influenced by the accuracy of the input data. Models require realistic cross sections for electron, ion, atom and photon collisions with the gas, as well as realistic probabilities for electron, ion, atom and photon interactions with electrode surfaces.…”
Section: The Role Of Ion-induced Electron Emission In Glow Dischargesmentioning
confidence: 99%
“…The transport of electrons (and ions) and the coupling of the charged particle transport to electromagnetic fields can be described using different levels of models ranging from macroscopic "fluid models" [1], to "hybrid models" [2], or to detailed kinetic models such as "particle in cell/Monte Carlo collision" (PIC-MCC) simulations [3]. Data needs for modeling depend on the level of description, but in all cases the needs are extensive.…”
Section: Introductionmentioning
confidence: 99%
“…After all fast electrons within MCC cycle have escaped from the volume or converted to the slow electrons, the ionization events data is interpolated into the grid points in order to determine the ionization rate profile. The ionization source profile is weighted to the actual value using the equation [11,17] S i,e = j (1 + 1/γ)∆x…”
Section: Simulation Of Fast Electronsmentioning
confidence: 99%
“…Within the kinetic (particle) methods, which provide quantitatively accurate results, particle species are simulated by the suitable number of super particles [6,7,2]. Hybrid methods are partially fluid and partially kinetic [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%